Federalism in Nepal: Legal Framework, Comparative Insights, and Implementation Challenges - Pokharel, Arjun Prasad (Academia Research Journal, 2026)
Adoption of federalism in Nepal through the 2015 Constitution marked a historic shift from a centralized unitary system to a three-tier federal structure comprising federal, provincial, and local governments. This transition was primarily driven by long-standing demands for ethnic, regional, and linguistic inclusion, as well as the need to address persistent inequalities in access to services, resources, and political representation. This study provides a comprehensive analysis of the legal composition of federalism in Nepal, with a comparative focus on selected South Asian and global federal models (India, Switzerland, Canada, and the United States). Utilizing secondary sources, including constitutional texts, policy documents, and scholarly literature, the research examines the constitutional division of legislative, executive, and fiscal powers, the degree of autonomy granted to provinces and local units, and the mechanisms for intergovernmental coordination. The findings reveal that while the 2015 Constitution formally establishes shared sovereignty and provincial autonomy, in practice, the federal government retains dominant control over key policy domains, financial resources, and administrative oversight, resulting in limited self-rule and weak shared-rule mechanisms at the subnational level. The study identifies persistent challenges including fiscal dependency of provinces, intergovernmental conflicts, capacity constraints at local levels, and tensions between ethnic-based and geographic-based federal principles. It argues that effective implementation requires constitutional clarification of residuary powers, stronger fiscal federalism provisions, and enhanced judicial mechanisms for dispute resolution. The comparative perspective highlights both the risks of central overreach (as seen in India) and the potential of balanced autonomy (as in Switzerland). The research concludes that while federalism has significantly advanced political inclusion and localized governance in Nepal, its long-term success depends on genuine power-sharing, equitable resource allocation, and the development of cooperative rather than competitive federal culture.